Mixed-Method Approach for Human Value Education in Inclusive Pre-Schools: Cultivating Peace to Mitigate Child Conflicts - Parwoto; Amir, Rudy; Amriani. H, Sri Rika; Syamsuardi; Herlina (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This study evaluates the implementation development of the PNKT-BD (Integrated Human Values Education Based on a Culture of Peace) model in the inclusive preschool setting of TK Teratai UNM Makassar, employing a mixed-method approach blending qualitative and quantitative research methodologies. The objectives were to integrate human values education into preschool activities, assessing its effectiveness in fostering a peaceful and inclusive environment. The study commenced with a needs assessment, revealing a high demand among teachers and parents for the PNKT-BD model despite challenges such as limited learning facilities. The model's development involved creating educational tools and conducting trials to evaluate their effectiveness. The model's validity, reliability, and practicality were assessed quantitatively, showing positive outcomes. Teachers played a key role as facilitators, promoting peaceful attitudes and inclusivity, supported by appropriate facilities. The findings suggest the PNKT-BD model is a viable approach for integrating human values in early childhood education, with potential applicability in various regions. The research also found that implementing the PNKT-BD model markedly improved children's social skills and conflict-resolution abilities. It was also observed that there was a significant increase in the inclusiveness and empathy displayed by children, both towards their peers and in the overall classroom environment. However, the study's focus on a single institution and reliance on self-reported data indicate the need for further research in diverse settings. The study underscores the importance of teacher training and resource development for the model's broader adoption.